1991
DOI: 10.1007/bf00197786
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of photosynthetic electron flow between CO2 and O2 reduction in a C3 leaf (Phaseolus vulgaris L.) at different CO2 concentrations and during drought stress

Abstract: Photosystem II chlorophyll fluorescence and leaf net gas exchanges (CO2 and H2O) were measured simultaneously on bean leaves (Phaseolus vulgaris L.) submitted either to different ambient CO2 concentrations or to a drought stress. When leaves are under photorespiratory conditions, a simple fluorescence parameter ΔF/ Fm (B. Genty et al. 1989, Biochem. Biophys. Acta 990, 87-92; ΔF = difference between maximum, Fm, and steady-state fluorescence emissions) allows the calculation of the total rate of photosynthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
196
1
8

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(225 citation statements)
references
References 23 publications
20
196
1
8
Order By: Relevance
“…Similar results have been documented in some woody species in analogous environments (Christiane andLudger 1999, Brodribb andField 2000). In addition, photosynthesis is partly limited by reduced intercellular CO 2 concentration due to stomata closure (Cornic andBriantais 1991, Quick et al 1992). Our investigation suggested that the indigenous species would have higher endurance to both air and soil drought than the non-indigenous ones when drought accidents occur.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results have been documented in some woody species in analogous environments (Christiane andLudger 1999, Brodribb andField 2000). In addition, photosynthesis is partly limited by reduced intercellular CO 2 concentration due to stomata closure (Cornic andBriantais 1991, Quick et al 1992). Our investigation suggested that the indigenous species would have higher endurance to both air and soil drought than the non-indigenous ones when drought accidents occur.…”
Section: Discussionsupporting
confidence: 80%
“…Our results also found support from the work of Cornic and Briantais et al, 1991 who observed that under severe dehydration stress, photosynthesis may be controlled by chloroplast capacity to fix CO 2 rather than diffusion characteristic. It has been shown in sunflower that non-stomatal limitation of photosynthesis may be related to reduced carboxylation efficiency, reduced RUBP regeneration or reduced amount of functional Rubisco.…”
Section: Discussionsupporting
confidence: 90%
“…A very good correlation has been observed between photoinhibition and a decreased ratio of variable to maximum fluorescence, i.e., the F v /F m ratio (Bolhar-Nordenkampf and Öquist, 1993). The Fv/Fm parameter has been correlated with the maximum quantum yield of photosynthesis (Björkman and Demmig-Adams, 1987;Bolhar-Nordenkampf and Öquist, 1993;Cornic and Briantais, 1991), reaching a maximum This kind of photoinhibition causes a decrease in photosynthetic efficiency, and may lead to limitations in daily carbon gain with a lower capacity for plant dry mass accumulation (Ögren and Sjöström, 1990). In this study, the dry weight of the shoots and roots under 0% shade was 24% and 22% lower than that under the 50% shade (Table 1).…”
Section: Resultsmentioning
confidence: 99%